2016
DOI: 10.20546/ijcrbp.2016.304.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Bioefficacy of Fungicides and Trichoderma spp. against Pestalotiopsis theae, Causing Grey Blight in Tea (Camellia sp.): An In Vitro Study

Abstract: A b s t r a c t A r t i c l e I n f oThe grey blight, caused by Pestalotiopsis theae is a serious problem in almost all tea growing regions of India. A large number of tea cultivars were found to be susceptible to this disease. Evaluation of four selected fungicides (carbendazim 12% a.i + mancozeb 63% a.i., hexaconazole 5 EC, copper oxychloride 50 WP and copper hydroxide 77 WP) have been found effective in suppressing the pathogen to the considerable degree under in vitro conditions. Results indicated that, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…The overall results are in line with the study by Kumhar et al (2016), where Hexaconazole and mixture of fungicides like Mancozeb, Carbendazim provided significant growth inhibition of over 70% against P. theae. Sanjay et al (2008) reported 6.6% of grey leaf blight incidence with Carbendazim application which was most effective in protection against P. theae.…”
Section: Figure 2 Effect Of Fungicidal Concentration On Mycelial Grow...supporting
confidence: 90%
See 2 more Smart Citations
“…The overall results are in line with the study by Kumhar et al (2016), where Hexaconazole and mixture of fungicides like Mancozeb, Carbendazim provided significant growth inhibition of over 70% against P. theae. Sanjay et al (2008) reported 6.6% of grey leaf blight incidence with Carbendazim application which was most effective in protection against P. theae.…”
Section: Figure 2 Effect Of Fungicidal Concentration On Mycelial Grow...supporting
confidence: 90%
“…Beside many other things Trichoderma also compete for nutrient and space against pathogen. The findings are synchronous with the result by Kumhar et al (2016) who reported significant inhibition of 61.5% by T. viride and 57% by T. harzianum against Pestalotiopsis theae. The increase in usage of Trichoderma isolates as bio-control agent is credit to its multifaceted advantages.…”
Section: Dual Culture Assay Of Trichoderma Spp and Pestalotiopsis Theaesupporting
confidence: 89%
See 1 more Smart Citation
“…is known to inhibit pathogenic fungal invasion via mycoparasitism, antibiosis, competition and lysis of fungal hyphae. Besides, Kumhar et al 26 tested Trichoderma viride and T. asperellum against the mycelial growth of Pestalotiopsis theae and found that these antagonistic fungi inhibited the growth of the fungus.…”
Section: Study Areamentioning
confidence: 99%
“…There was no incidence of anthracnose and crown rot [41]. It was noted that T. viride, T. harzianum, and T. asperellum were potential antagonists for the management of F. solani and Pestalotiopsis theae causing dieback and grey leaf spot disease of tea [48,49]. Foliar spray of T. asperellum and T. atroviride could manage the dieback disease of tea (Camelliasp) and enhance the vegetative growth in terms of more number of pluckable shoots [50].…”
Section: Management Through Soil Treatment With Trichoderma Sppmentioning
confidence: 99%